Kembang Sejati Chalet (KSC) Booking System - Roslay, Faizuddin Shah; Mohd Sahid, Zanes (Applied Information Technology And Computer Science, 2026)
The hospitality industry’s growth necessitates enhanced operational efficiency and customer experience, which Kembang Sejati Chalet (KSC) currently struggles with due to its manual booking system. This system leads to booking errors, lack of real-time availability updates, limited customer accessibility, and a time-consuming reservation process. To address these challenges, an agile methodology is employed to develop a web-based booking system featuring real-time availability updates, reservation tracking, and payment processing. Built using PHP and MySQL frameworks, the system ensures scalability and user-friendliness. Its implementation at KSC aims to eliminate manual errors, streamline operational processes, and enhance customer satisfaction. By providing a reliable platform for managing reservations, the system will improve service delivery, increase operational efficiency, and support the chalet’s long-term growth and reputation in the competitive hospitality sector. The project underscores the importance of technological innovation in driving success in the industry.